2004
DOI: 10.1079/bjn20041122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary flavonols on oestrogen receptor transactivation and cell death induction

Abstract: Consumption of fruits and vegetables has been associated with cancer prevention; flavonoids are widely distributed in plant foods and considered to be the active ingredients. Quercetin and kaempferol are two of the most commonly found dietary flavonols, and have been reported to prevent cancer. We have previously reported that the isoflavone genistein and the flavone baicalein exert differential actions on the oestrogen receptor (OR) a in HepG2 cells. Because of the structural resemblance to both isoflavone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…However, it should be noted that the membrane levels of DR5 or DR4 were not assessed in this study, so the absence of blockade after DR4 silencing could be explained by a lack of DR4 at the cell surface. Consistent with a previous study [72], Bcl-2 was surprisingly upregulated by kaempferol without compromising TRAIL-induced cell death. Association of kaempferol with TRAIL was also effective in the prostate carcinoma cell line PC-3 [71], and in three out of seven gliomas [73].…”
Section: Flavonolssupporting
confidence: 80%
“…However, it should be noted that the membrane levels of DR5 or DR4 were not assessed in this study, so the absence of blockade after DR4 silencing could be explained by a lack of DR4 at the cell surface. Consistent with a previous study [72], Bcl-2 was surprisingly upregulated by kaempferol without compromising TRAIL-induced cell death. Association of kaempferol with TRAIL was also effective in the prostate carcinoma cell line PC-3 [71], and in three out of seven gliomas [73].…”
Section: Flavonolssupporting
confidence: 80%
“…Human intervention trials with isolated flavonols have demonstrated an anti-hypertensive effect. Besides their high antioxidant capacity, flavonols are also known to interact with estrogenic receptors [12]. Various studies have shown that flavonols have properties that alleviate several diseases, including inflammation and cancer [13].…”
Section: Introductionmentioning
confidence: 99%
“…The cyclization of esters of anthranilic acids and 2-hydroxyketones has been studied for some time. Originally, the formation of a seven-membered ring was described in the literature. , It was proved later that rearrangement to a six-membered ring takes place leading to a general, simple, and efficient synthetic entry into 2-substituted-3-hydroxy-4(1 H )-quinolinones. These compounds are interesting because they can be considered as isosteres of flavonols, which are well-known for their applications in medicine 6 and for the various kinds of biological activity they exhibit . For this reason, and in an effort to improve the synthesis, the course of the cyclization of anthranilamides 2 under various conditions was studied.…”
mentioning
confidence: 99%
“…[3][4][5] These compounds are interesting because they can be considered as isosteres of flavonols, which are well-known for their applications in medicine 6 and for the various kinds of biological activity they exhibit. 7 For this reason, and in an effort to improve the synthesis, the course of the cyclization of anthranilamides 2 under various conditions was studied. Scheme 1 outlines the reaction conditions and final products.…”
mentioning
confidence: 99%